2014
DOI: 10.5770/cgj.17.54
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Rehabilitation Patients’ Perceptions of Unit Dining Locations

Abstract: BackgroundEating together is promoted among hospitalized seniors to improve their nutrition. This study aimed to understand geriatric patients’ perceptions regarding meals in a common dining area versus at the bedside.MethodsAn exploratory qualitative study was conducted. Open-ended questions were asked of eight patients recruited from a geriatric rehabilitation unit where patients had a choice of meal location.ResultsEating location was influenced by compliance with the perceived rules of the unit, physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…Some of the reasons for this included the participants having a perceived increased control over their personal time when eating at the bedside or a feeling of poor quality of interaction when eating in the dining room. 4 Interestingly, those who reported enjoying the dining room valued the social aspect of eating in a pleasant environment, with the participants staying at the bedside reporting to feel lonely at times. 4 Given the improved energy and protein intake seen in this study when patients ate in the dining room, it might be important to engage patients choosing to eat at their bedsides in strategies to improve their participation in the dining room.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the reasons for this included the participants having a perceived increased control over their personal time when eating at the bedside or a feeling of poor quality of interaction when eating in the dining room. 4 Interestingly, those who reported enjoying the dining room valued the social aspect of eating in a pleasant environment, with the participants staying at the bedside reporting to feel lonely at times. 4 Given the improved energy and protein intake seen in this study when patients ate in the dining room, it might be important to engage patients choosing to eat at their bedsides in strategies to improve their participation in the dining room.…”
Section: Discussionmentioning
confidence: 99%
“…These include protected mealtimes, feeding assistance, and the ‘red tray' initiative, where patients at risk of malnutrition are provided meals on red trays which act as a visual indicator to staff that these patients require additional support and assistance to complete their meals . Communal dining is also recognised as a nutritional model of care, and studies have demonstrated that an improvement in eating environment by changing the surrounds and facilitating a social dining experience may positively impact the amount of food consumed …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…have prepared a qualitative assessment of patient’s perceptions of dining locations in a rehabilitation ward. (6) …”
mentioning
confidence: 99%